John Dewey on History in Elementary and Secondary Education - George C. Stone (Educational Considerations, 1973)
Just what did John Dewey say about elementary education? About secondary education? About higher education? With particular regard to the study of history, philosopher Stone summarizes Dewey's positions for each area.